2011
DOI: 10.1016/j.leaqua.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of stereotypical beliefs about leadership styles: Is transformational leadership a route to women's promotion?

Abstract: An exploration of stereotypical beliefs about leadership stylesVinkenburg, C.J.; van Engen, Marloes; Eagly, A.H.; Johannesen-Schmidt, M.C. Published in:The Leadership Quarterly Document version:Publisher's PDF, also known as Version of record General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
191
1
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(231 citation statements)
references
References 49 publications
(48 reference statements)
14
191
1
9
Order By: Relevance
“…As such, this body of work is equally important today and researchers (e.g. Billing, 2011;Cabrera, 2009;Corby and Stanworth, 2009;Maxwell, 2009;Priola and Brannen, 2009;Vanderbroeck, 2010;Vinkenburg et al, 2011) continue to be intrigued by women's accounts of their gendered experiences in management and the processes which both facilitate and limit their career opportunities.…”
Section: Women's Voice Literaturementioning
confidence: 99%
“…As such, this body of work is equally important today and researchers (e.g. Billing, 2011;Cabrera, 2009;Corby and Stanworth, 2009;Maxwell, 2009;Priola and Brannen, 2009;Vanderbroeck, 2010;Vinkenburg et al, 2011) continue to be intrigued by women's accounts of their gendered experiences in management and the processes which both facilitate and limit their career opportunities.…”
Section: Women's Voice Literaturementioning
confidence: 99%
“…Reuvers et al, 2008;Eagly and Johnson, 1990) have shown that women and men (although equally successful as leaders) have di erent leadership styles -while women are more focused on employee well-being, men focus on domination over others and solving tasks, which corresponds to stereotypical male and female behaviour. A recent study by Vinkenburg et al (2011) investigated stereotypes about the importance of leadership styles for the promotion of women and men to di erent levels in organizations. Inspirational motivation (optimism and excitement about the future) was seen as more important for men than women, particularly for a promotion to CEO.…”
Section: Social Roles Of Men and Womenmentioning
confidence: 99%
“…In this research, some of the challenges that women administrators experienced were resonated with most previous literature from around the world; most of the challenges include challenges regarding women's prescribed duties and their professional academic demands and heavy workload as lecturers and administrators (Luke et al, 2003;Lee, 2001;Letherby, 2006;Eagly, 2007;Madsen, 2008Madsen, , 2012Neale & Özkanlı, 2010;Eagly et al, 2011;Ramsay and White, 2011;Blackwoodet al, 2011;Nguyen, 2013;Morley, 2014;Baruch et al, 2014;Peterson, 2016). However, the results of this study make a valuable contribution to the discussion, because the findings reveal the specific influence of socio-cultural values in the Iranian context on challenges for women academicians in senior administrative positions.…”
Section: Findings and Discussionmentioning
confidence: 81%
“…Many personal attributes which are more likely to help women in accomplishing duties in administrative positions include collaborative style Madsen, 2008), more people-oriented (Eagly et al, 2001;Vinkenburg et al, 2011), assertiveness (Williams, 1993), adaptability, determination, self-motivation, confidence, and independence (Wolverton & Gmelch, 2002;Lam, 2006;Ismail & Rasdi, 2006;Madsen, 2008;Wajcman, 2013;Oplatka, 2006;Eagly & Carli, 2007;Heilman, 2001;Schein, 2001), and having a higher commitments (Johnsrud & Heck, 1994;Lam, 2009;Wajcman, 2013). Many scholars demonstrated that women having the above mentioned personal attributes are more likely to tolerate higher responsibility career positions in higher education.…”
Section: Individual Factorsmentioning
confidence: 99%